Liberalizm a szanse pokoju na świecie. Refleksje Karla Jaspersa - Citkowska-Kimla, Anna (Przegląd Politologiczny, 2018)
The paper touches on the topic of optimism, allowing for a thesis of the peaceful coexistence of states to be proposed. This type of thinking was represented by the German philosopher and psychiatrist Karl Jaspers. Jaspers took the view that philosophy brings about political consequences that need to be observed and examined. He was influenced by Max Weber, from whom he adopted the idea of the salvation of Western heritage, embodied in the spirit of liberalism, freedom and diversity of private life. According to Jaspers, Germans should abandon their desire for military supremacy in favor of the dissemination of such universal ideas as freedom. In the interwar period Jaspers wrote a book about the spiritual situation of his times where he touched on the issue of the outcomes of technological progress for the existential dimension of man, who enjoys freedom on the one hand, and is responsible for himself on the other. He concluded by saying that in the face of such technical developments warfare poses a threat to biological survival and to freedom, since it destroys human self-responsibility. Jaspers noticed the problem of an individual being threatened by alienated social institutions, and as a consequence he proposed the thesis of the depersonalization of individual existence. The totalitarian system Jaspers had experienced encouraged him to revise the theoretical aspects and to develop a competitive, libertarian solution. Jaspers strongly emphasized individualism and the responsibility of individuals whose present influences the future. Jaspers’ ideas may be deemed to be remote from realism, since liberalism is a golden mean, neither preventing international wars nor appeasing political national arenas.